The lack of trust and the utopia of consent in education policy - Φραγκούλης Γιώργος (The Greek Review of Social Research, 2010)
In this paper, it is argued that, in the Greek educational system, the main feature of the debate about education policy is the complete absence of trust among the participating bodies. It is argued that this lack of trust is related to the way that social relations have been established in the Greek educational system, and constitutes a major factor that makes even more difficult to achieve consent in education policy. The debate for the access system to higher education is a characteristic example of the incapability to achieve consent, even to conduct the debate itself.